A Physio-Anatomical Study on Anukta Srotas with special reference of Ashruvaha Srotas - Sourav Sharma; Maneela Sharma (AYUSHDHARA, 2023)
The number of Srotas are specifically compared with the number of Bhavas in our body. In our body, there is Aparisankheya (innumerable) bhava, so the number of Srotas is also Aparisankhey. In Strotovimaniyaadhyaya, where as many more Srotas have been mentioned in our classics such as Ashruvaha Srotas, Lasikavah Srotas, Sandnyavaha Srotas, etc., we get the specifics of only thirteen Srotas of which Mulasthnadi have not been clarified. Awareness about these Anukta Srotas is needed to treat the diseases of these Srotas. Detailed knowledge of 13 Srotas is enough to believe, visualize and manage the diseases of Laksha-Alaksha Anukta Srotas, according to Acharya Srotas are the Avakashas, which are Abhivahanshila that circulate in our body and travel through their Mulasthanas, thus, their Mulasthana must be verified to learn Anukta Srotas. The whole body is composed of Srotas (micro and macro channels) according to Ayurvedic literature, which transports all sorts of materials throughout the body. It is important that these pathways, both micro and macro, remain intact for proper body function. We found that there is a detailed description of Srotas in Samhita. Srotas are connected to each-other so that other Srotas are also affected when one Srotas is vitiated. The structures that hold or circulate the Doshas and tissues (Dhatu) or their components to the different organs are the Srotas.